2016
DOI: 10.3329/bjar.v40i4.26930
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of raised bed technology in some selected locations of Rajshahi District of Bangladesh

Abstract: The study evaluated the adoption and farmers’ practice of raised bed technology at farm level since the close of the Soil Management Collaborative Research Support Program (SMCRSP) through a follow-up survey conducted at Durgapur Upazila of Rajshahi district. Data for the study were collected from 195 adopters and 65 non-adopters through a pre-tested interview schedule during May, 2011. The survey findings showed that the raised bed technology had a strong demonstration effect and were adopted well (56%) by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Salahin et al (2014) reported significantly higher crop yield from the third continuous crop under all minimum soil disturbance planting options by VMP, which was similar to a report by Islam et al (2011). Results from many trials in Bangladesh with other minimum soil disturbing planters also supported the yield increases (Johansen et al, 2012;Miah et al, 2010;Vance et al, 2014).…”
Section: Crop Yieldmentioning
confidence: 69%
See 2 more Smart Citations
“…Salahin et al (2014) reported significantly higher crop yield from the third continuous crop under all minimum soil disturbance planting options by VMP, which was similar to a report by Islam et al (2011). Results from many trials in Bangladesh with other minimum soil disturbing planters also supported the yield increases (Johansen et al, 2012;Miah et al, 2010;Vance et al, 2014).…”
Section: Crop Yieldmentioning
confidence: 69%
“…Planting wheat on beds was gained popularity in Durgapur and Charghat upazilas in Rajshahi district with about 98% of farmers using this procedure (Miah et al , 2014). However, due to unavailability of mechanised planters, 96% of those farmers prepared land by CT and then formed the beds manually, which is costly and labour intensive (Miah et al , 2014). BP using the VMP was able to achieve satisfactory plant density in most cases, although the plant population was lower than other single pass tillage options, for example, with wheat at Godagari in Rajshahi district.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bed and furrow irrigation system, the plants are grown on raised beds which not only use irrigation water more efficiently but also ensure better crop growth (Berkout, Yasmeen, Maqsood, & Kalwij, 1997). The bed planting system facilitates weed control, allows mechanical cultivation of crops, and improves the stands of the plants (Miah, Hossain, Duxbury, & Lauren, 2015). It also provides an opportunity for easy field entry resulting from row orientation on the beds, efficient management of irrigation water, and also requires less labour (Fischer, Sayre, & Monasterio, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although a great deal of knowledge on the role of MRBT in improving water-use efficiency has been gained from irrigation, agronomic, and economic studies, too few studies have sought to understand how different agricultural livelihood contexts shape adoption rates and drivers affecting farmers' adoption of MRBT. In most precedent studies on adoption analyses, either on MRBT or other agricultural innovations, drivers of adoption were inferred from econometric analyses of one household/farm sample selected for the entire study area; hence, the revealed cause-effect relationships were also applied uniformly over the study area [14][15][16][17][18]. Indeed, the causal relationships defined in that way (one sample for the study area) were validly applied for an average household or farm of the area (located in the centroid of the multivariate sample).…”
Section: Introductionmentioning
confidence: 99%